Beam optics study for a potential VHEE beam delivery system - Robertson, CS; Burrows, PN; Dosanjh, M; Et al. (JACoW Publishing, 2022)
VHEE (Very High Energy Electron) therapy can be superior to conventional radiotherapy for the treatment of deep seated tumours, whilst not necessarily requiring the space and cost of proton or heavy ion facilities. Developments in high gradient RF technology have allowed electrons to be accelerated to VHEE energies in a compact space, meaning that treatment could be possible with a shorter linac. A crucial component of VHEE treatment is the transfer of the beam from accelerator to patient. This is required to magnify the beam to cover the transverse extent of the tumour, whilst ensuring a uniform beam distribution. Two principle methodologies for the design of a compact transfer line are presented. The first of these is based upon a quadrupole lattice and optical magnification of beam size. A minimisation algorithm is used to enforce certain criteria on the beam distribution at the patient, defining the lattice through an automated routine. Separately, a dual scattering-foil based system is also presented, which uses similar algorithms for the optimisation of the foil geometry in order to achieve the desired beam shape at the patient location.